PERLINDUNGAN HUKUM BAGI TENAGA KERJA ASING TERHADAP PELANGGARAN PERJANJIAN KERJA WAKTU TERTENTU (STUDI KASUS PUTUSAN PENGADILAN HUBUNGAN INDUSTRIAL NOMOR: 274/PDT.SUS-PHI/2015.PN.JKT.PST JO PUTUSAN MAHKAMAH AGUNG NOMOR: 697 K/PDT.SUS-PHI/2016) - Cecilia Puspa Halim; Andari Yurikosari (Jurnal Hukum Adigama, 2018)
Law Number 13 of 2013 on Manpower has clearly regulate about work relationship between a foreign labor and Employers of Foreign Labor is only for fixed time employment relations which is based on a Fixed Term of Labor Contract. Article 57 of the Manpower Law stated that a Fixed Term of Labor Contract must be made in writing and must be written in the Indonesian language with Latin alphabets, if not, the agreement shall be reg  arde d as a Working Agreement Uncertain Time. A Fixed Term of Labor Contract shall be made based on specified time stated in the work agreement. The author was purposed to find out about how violation of Fixed Term of Labor Contract for Foreign Labor according to Manpower Law, case example: verdict of settlement of industrial relation court number 274/Pdt.Sus-PHI/2015.PN.JKT.PST Juncto Verdict of supreme court number 697K/Pdt.Sus-PHI/2016 and about legal protection of Foreign Labor who do not have the Fixed Term of Labor Contract in accordance with the Law Number 13 of 2003 on Manpower. The author research this problem using nomative researching method supported by interview data of experts. The author analysis that violations of Fixed Term of Labor Contract done by PT Wira Pamungkas Pariwara againts Lau Chak Loong are the Fixed Term of Labor Contract was made and sign in foreign language and didn't contain fixed time agreement caused ambiguous foreign labor status to claim his rights.